CFIT PREVENTION WITH COMBINED ENHANCED FLIGHT VISION SYSTEM AND SYNTHETIC VISION SYSTEM - Iradukunda, Klarisse; Averyanova, Yuliya (Proceedings of National Aviation University (archive), 2021)
This paper aims to combine two vision systems as a new technology to suggest the improvement in the continuing problem of Controlled Flight into Terrain (CFIT) accidents. A combined enhanced flight vision system and synthetic vision system seems to hold the solution, while it unhesitatingly accommodated to the commercial and General aviation instrument environment if pilots are getting minimal instrument training. This research shows the benefit of combined enhanced flight vision and synthetic vision systems based on analysis of the accident that occurred in 2013 on approach at Birmingham-Shuttlesworth International Airport. It is shown that the use of a combined system, could have prevented this accident. The head-up display is taken to facilitate this technology to the pilot to be able to see and read accurately using sky lenses.